Más allá del mar, un inmenso jardín. El trato a la figura de Rafael del Riego en la prensa de México, Colombia y Buenos Aires tras su muerte (1823-1830) - Alberto Cañas de Pablos (Cahiers de Civilisation Espagnole Contemporaine)
Rafael del Riego after his pronunciamento in 1820 became a political symbol who embodied the system of Spanish Liberal Triennium, a reference inside and outside his country. Because of that reason the news of his execution in November 1823 travelled fast around the world. The case of American territories that were fighting for sparing from their mother country presents several special features, because they were at the same time next and far from what was happening in Spain, in different ways. Because of that, the perception towards Riego and his fate after his death is very relevant to understand that period. In that sense, press is an enriching primary source, so several representative publications have been chosen. They come from Mexico, Colombia, and Buenos Aires Province, featuring different political realities. Lastly, the time span encompasses seven years, from the hero’s death in 1823 until the end of the decade, in 1830.